Hemophagocytic Syndrome Which Developed During Treatment of Community Acquired Pneumonia: A Case Report - Esengül Keleş; Hamza Yazgan; Arzu Gebeşçe (Haseki Tıp Bülteni, 2013)
Abstract: Hemophagocytic syndrome (HLH), which occurs due to over activation and proliferation of the T-cells and macrophages resulting in massive hypercytokinemia, is a life threatening condition accompanied by systemic inflamatory diseases. HLH can develop secondary to malignancy, radical stress, metabolic diseases, immunodeficiency, and collagen tissue disorders as well as viral, bacterial and parasitic infections. A 6-year-old patient had progressive clinical and laboratory impairment during the treatment of community-acquired non-specific pneumonia. The diagnosis of HLH was established based on bone marrow aspiration which revealed macrophages which phagocytosed erythrocytes and leukocytes, and, thus, the treatment was started immediately. This case is reported due to the rarity of HLH developing during the treatment of pneumonia. (The Me¬di¬cal Bulletin of Haseki 2013;51:183-5)